THE LEVEL OF APPLICATION OF BIOSECURITY IN BROILER FARMS IN THE CITY OF PALANGKA RAYA - Sandriya, Ardi; Sujoko, Heri; Wibowo, Satrio; Silitonga, Lisnawaty; Yuanita, Iis; Aritonang, Nopita (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023DO - 10.24843/bulvet.2023.v15.i05.p26, 2023)
This study aims to determine the implementation of the application of biosecurity carried out by broiler breeders in the city of Palangka Raya. This research is field research using a survey method and location selection was carried out by purposive sampling taking into account proximity, affordability, and the largest number of broiler breeders in the area. This research was conducted in 17 broiler chicken coops, the coop managers were interviewed and the coops were the object of observation for the application of biosecurity. The variables of this study are the application of biosecurity isolation, the application of biosecurity in controlling the traffic of people, livestock, and vehicles; as well as the application of cage sanitation and environmental biosecurity. The data analysis used was descriptive statistical analysis with an assessment of the biosecurity implementation category which was divided into 3, namely good: , enough: , and poor: . The results showed that the characteristics of broiler breeders in the city of Palangka Raya were very diverse, which could be observed from education, experience in raising livestock, and the number of livestock in each production period. The application of biosecurity isolation in the less category is 3 cages (18%), 4 cages (82%) is sufficient, and 0 cages (0%) is good. The implementation of cage sanitation was lacking 4 cages (24%), 8 cages (47%) were sufficient, and 5 cages were good (29%). The application of traffic control biosecurity is in the category of less than 3 cages (18%), enough 10 cages (58%), and good 4 cages (24%). It was concluded that the overall application of biosecurity in the City of Palangka Raya was in the sufficient category. It is necessary to increase the application of biosecurity to prevent the entry and exit of diseases on a farm.